Seaweed Biocomposite as a Green Construction Material - Oh, Jia Wei (Universiti Teknologi PETRONAS, 2017)
The choice of topic is inspired by growing need of finding more sustainable and environmentally friendly materials in modern building industry. The answer for this need can be new biological insulation materials, and seaweed is one of the most promising one. This research aims to determine the compressive strength of mortar cube based on a replacement ratio of 5% & 15% by seaweed (Gracilaria species). The sample was washed until the pH value is neutral. Later, the samples were oven dried at 105C for 24 hours and some are continued to be burnt at 600C for 3 hours to obtain the sample in granular and powder form. The seaweed granules and seaweed ashes were then analyzed and characterization tests were performed using brunauer, emmett and teller (BET), field emission-scanning electron microscope (FESEM), x-ray diffraction (XRD) and differential scanning calorimetry (DSC). Water absorption test used to determine the total volume of permeable void will be described as well. The sample was then incorporated into the mortar and the compressive strength was determined at 3,7,14 and 28 days respectively. After 28 days, the compressive strength test shows that 15% burnt sample has the highest compressive strength surpassing the control mix design. Therefore, seaweed which is eco-friendly has the potential to act as a substitute for green construction material.